2017
DOI: 10.4172/2150-3508.1000231
|View full text |Cite
|
Sign up to set email alerts
|

Changing of Sea Surface Temperature Affects Catch of Spanish Mackerel Scomberomorus Commerson in the Set-Net Fishery

Abstract: This paper reviews the Spanish mackerel Scomberomorus commerson landing status of the set-net fishery and changing sea surface temperature (SST) in Nha Trang city, Vietnam in the 12th year period. The observation of both catch and individual weight showed a general trend of declining between 2005 and 2016. Catch yield of set-net fishery significantly depended on season and moon phase resulting from highest harvesting in April and May, as well as in the new moon and last quarter of phases. SST in the Nha Trang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 10 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The catch of S. commerson is significantly related to sea surface temperature (SST) changes; the recommended SST and salinity for achieving optimal S. commerson catch rates (CRs) are 14-31 • C and 23-35 psu, respectively (Niamaimandi et al, 2015;Nguyen and Nguyena, 2017). Several studies have suggested that chlorophyll-a concentrations and sea surface height (SSH) influence the distribution patterns of pelagic fish species and the variability of pelagic fish species abundance (Hazen et al, 2013;Liao et al, 2018;Lan et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…The catch of S. commerson is significantly related to sea surface temperature (SST) changes; the recommended SST and salinity for achieving optimal S. commerson catch rates (CRs) are 14-31 • C and 23-35 psu, respectively (Niamaimandi et al, 2015;Nguyen and Nguyena, 2017). Several studies have suggested that chlorophyll-a concentrations and sea surface height (SSH) influence the distribution patterns of pelagic fish species and the variability of pelagic fish species abundance (Hazen et al, 2013;Liao et al, 2018;Lan et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Another area of study such as in Nha Trang bay, Vietnam reported that the total landing of the main species, Spanish mackerel, dramatically decreased from approximately 23,457 kg in 2005 to only 6,998 kg in 2016. The moon phase, year, and sea surface temperature (SST) are found to be significant factors to the variation of Spanish mackerel catch of set net fishery (Nguyen and Nguyena, 2017).…”
Section: Introductionmentioning
confidence: 99%